2021
DOI: 10.1093/humrep/deab212
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst formation is similar in obese and normal weight women: a morphokinetic study

Abstract: STUDY QUESTION Does the embryo cleavage pattern and rate of blastocyst formation differ between normal weight and obese women undergoing IVF? SUMMARY ANSWER Embryo morphokinetic development, final blastocyst formation rate and blastocyst morphology do not differ between obese and normal weight women. WHAT IS KNOWN ALREADY Female obesity has been related to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Other studies suggest that high BMI is not associated with the number or proportion of aneuploid, mosaic, or euploid embryos in this large cohort of patients undergoing IVF with PGD/PGS, implying that the potential adverse effect of excess weight on reproductive outcomes was independent of the ploidy status of the embryo cohort (14). This was also con rmed in the retrospective cohort study of 3,316 ICSI cycles where authors showed that blastocyst formation and embryo morphogenetics were not affected by female obesity, suggesting that the poorer IVF outcomes for such women are probably due to low endometrial receptivity (15). On the contrary, a higher BMI was not favourable for forming high-quality embryos in the ICSI cycle ( 16).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Other studies suggest that high BMI is not associated with the number or proportion of aneuploid, mosaic, or euploid embryos in this large cohort of patients undergoing IVF with PGD/PGS, implying that the potential adverse effect of excess weight on reproductive outcomes was independent of the ploidy status of the embryo cohort (14). This was also con rmed in the retrospective cohort study of 3,316 ICSI cycles where authors showed that blastocyst formation and embryo morphogenetics were not affected by female obesity, suggesting that the poorer IVF outcomes for such women are probably due to low endometrial receptivity (15). On the contrary, a higher BMI was not favourable for forming high-quality embryos in the ICSI cycle ( 16).…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, women with higher PRG levels were more likely to give birth to a girl, implying that perhaps the role of endometrial PRG exposure on the day of embryo transfer should be considered as a determining factor of implantation in this group of patients (15). Both PRG supplementation during the luteal phase and early pregnancy improve the number of live births after frozen embryo transfer (12,21,22).…”
Section: Discussionmentioning
confidence: 54%
“…In contrast, in the study of 1889 infertile couples by Kim et al [3], obese patients presented a higher blastocyst formation rate than their normal weight counterparts, hence representing opposite findings. More recently, Bellver et al [40 ▪ ] morphokinetically evaluated all the embryos obtained from ICSI cycles in 2,882 women, including 140 underweight, 1,989 normal weight, 548 overweight and 145 obese women. No differences were detected in blastocyst quality among the different BMI groups, and only an initially slower embryo development was seen in obese women, which became normal at blastulation.…”
Section: Cause Of Miscarriage In Obese Womenmentioning
confidence: 99%
“…Only transfers of a single euploid frozen blastocyst using own oocytes were included. Ovarian stimulation, oocyte retrieval, intracytoplasmic sperm injection, embryo culture, embryo biopsy, genetic study and embryo vitrification and warming were carried out according to standard protocols, as previously described (Bellver et al, 2021;Cozzolino et al, 2021).…”
Section: Study Populationmentioning
confidence: 99%